Head-to-Head Comparison between Indonesia and Taiwan to Provide Professional Vocational Teachers in Fashion Education - Siti Zahro (Jurnal Pendidikan Teknologi dan Kejuruan, 2019)
Teachers must have three major components, including content knowledge, pedagogical knowledge, and pedagogical content knowledge. A teacher of Technology and Vocational Education and Training (TVET) has an important role in the learning process of students in vocational education because the quality of teachers determines that of graduates of vocational schools. Therefore, the teacher candidates in TVET must have work experiences in the industry, so that they produce students who have high quality and can compete in the labour market. The teacher candidates must be prepared through a process of quality education to become professional teachers in the future. Providing professional fashion teacher candidates is not easy, for it takes a certain curriculum content and long processes. With literature review method with head-to-head approach, the paper aims to understand how to provide professional teachers for fashion department. Furthermore, the curriculum of fashion teacher candidates in Taiwan and Indonesia, the line of becoming professional TVET teacher, and future framework for establishing professional teachers in Indonesia were discussed